PENGARUH ATMOSFER KEDAI KOPI TERHADAP EMOSI DAN KEPUTUSAN PEMBELIAN ULANG - Vania Pramatatya; Mukhamad Najib; Dodik Ridho Nurrochmat (School of Business, Bogor Agricultural University (SB-IPB), 2015)
This research aims to identify the effect of coffeeshop atmospheric stimuli on repeat-purchase decisions through consumers’ emotions in their minds. The object of this research took place in Rumah Kopi Ranin, a coffee shop in Bogor town with a unique atmosphere concept as one of their strategies in marketing of Indonesian’s specialty coffee and to welfare the Indonesian coffee farmers. This research was conducted to 166 patrons of Rumah Kopi Ranin by convenience sampling method. The data is processed by using a statistical method called PLS (Partial Least Squares) to test the hypothesis of the variables’ influences such as atmospherics stimuli factors (exterior, layout, interior, sound, scent, temperature and human variables), emotions (Pleasure, Arousal, Dominance), and the repeat-purchase decisions. Findings indicate that interior and consumers’ emotions influences consumer’s positive affect on repurchase decisions, especially the interior. While the human variable have a positive influence on consumers’ emotions, which means patrons view the positive emotions from the atmosphere is very important in determining their repeat purchase decisions.Keyword: specialty coffee, coffee shop, consumers’ emotions, repeat-purchase decisions, PLSABSTRAKPenelitian ini bertujuan untuk mengidentifikasi pengaruh stimulus atmosfer kedai kopi terhadap keputusan pembelian ulang melalui emosi di benak konsumen. Objek penelitian ini mengambil lokasi di Rumah Kopi Ranin, sebuah kedai kopi di Kota Bogor dengan konsep atmosfer yang unik sebagai salah satu strategi mereka dalam memasarkan kopi spesial Indonesia dan mensejahterakan petani kopi Indonesia. Penelitian ini dilakukan kepada 166 pengunjung Rumah Kopi Ranin dengan metode convenience sampling. Data diolah dengan menggunakan metode statistika yang disebut PLS (Partial Least Squares) untuk menguji hipotesis dari pengaruh variabel-variabel seperti faktor stimulus atmosfer (Eksterior, layout, interior, suara, aroma, temperatur, dan human variable), emosi (Pleasure, arousal, dominance), dan keputusan pembelian ulang. Temuan menunjukan bahwa interior dan emosi konsumen berpengaruh positif signifikan terhadap keputusan pembelian ulang, terutama interior. Sementara itu, human variable berpengaruh positif signifikan terhadap emosi yang berarti pengunjung memandang bahwa emosi positif dari atmosfer sangat penting dalam menentukan keputusan pembelian ulang mereka. Kata kunci: kopi spesial, kedai kopi, emosi konsumen, keputusan pembelian ulang, PLS